Examination of exclusion criteria in total knee arthroplasty rehabilitation trials: influence on the application of evidence in day‐to‐day practice. Issue 6 (24th March 2021) - Kittelson, Andrew J.; Loyd, Brian J.; Graber, Jeremy; Himawan, Michael A.; Waugh, Dawn; Davenport, Jacqueline; Hoogeboom, Thomas J.; Stevens‐Lapsley, Jennifer
Abstract: Objective: Total knee arthroplasty (TKA) rehabilitation trials use exclusion criteria, which may limit their generalizability in practice. We investigated whether patients seen in routine practice who meet common exclusion criteria recover differently from TKA compared to research‐eligible patients. We hypothesized that research‐ineligible patients would demonstrate poorer average postoperative function and slower rate of functional recovery compared to research‐eligible patients. Methods: Patient characteristics and exclusion criteria were extracted and summarized from trials included in the three most recent systematic reviews of TKA rehabilitation. Trial participant characteristics were compared to a clinical dataset of patient outcomes collected in routine TKA rehabilitation. Where possible, individual exclusion criterion from the trials were applied to the clinical dataset to determine "eligible" and "ineligible" groups for research participation. Postoperative functional outcomes including the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Timed Up and Go (TUG) were compared between "eligible" and "ineligible" groups using mixed effects models. Results: 2, 528 participants from 27 trials were compared to 474 patients from the clinical dataset. Research participants were older, with lower Body Mass Index than patients in the clinical dataset. Many patients in the clinical dataset would be "ineligible" for research participation based upon common exclusion criteria from the trials. Differences were observed in average postoperative functioning between some "eligible" and "ineligible" groups in the clinical dataset. However, no differences were observed in functional recovery rate between groups, except for patients with diabetes whose TUG recovered more slowly than their "eligible" counterparts. Conclusions: Many patients in the clinical dataset were "ineligible" for research participation based upon common TKA rehabilitation trial exclusion criteria. However, the postoperative recovery rate did not differ between "eligible" and "ineligible" groups based on individual exclusion criterion—except for individuals with diabetes. This suggests that both clinical and research populations may recover similarly from TKA.